Implementasi Pembelajaran Interaktif Berbasis Game Edukatif Melalui Media Smart TV Anak Usia Dini Di RA Tadika Adnani - Ummi Kalsum; Riadoh Riadoh; Fitri Mahrani Siagian; Normaliza Normaliza; Ira Wardani; Nur Fadilah; Putri Kesawan; Annisa Wahyuni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
This study aims to describe the implementation of interactive learning based on educational games through Smart TV media for early childhood at RA Tadika Adnani. This research employed a qualitative method with a case study approach. The research subjects consisted of one teacher and 30 early childhood students at RA Tadika Adnani. Data were collected through observation, interviews, and documentation. The data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The results showed that the use of educational games through Smart TV increased children's engagement in the learning process. The materials presented included the introduction of Hijaiyah letters, Asmaul Husna, daily prayers, and cognitive games such as matching colors and pictures presented audiovisually. During the learning process, the teacher played an active role by asking questions, motivating children to respond, and encouraging students to practice the materials they learned. Game-based learning made children more enthusiastic, active, and confident in participating in classroom activities. Positive impacts were observed in the development of cognitive, language, social-emotional, as well as religious and moral values of early childhood. Therefore, the use of educational games through Smart TV media can be an effective and innovative learning strategy in early childhood education.